Analysis of Fishermen's Income in The Seribu Archipelago - Sudiarti, Sri; Syarvina, Wahyu; Yanti, Nursantri (Universitas Pasundan, 2024)
This region of Indonesia has great potential for national development and is aimed at increasing economic growth for the better. The low welfare of fishermen, especially traditional fishermen, is a problem that hinders the development of fisheries zones. The purpose of this article is to describe the partial and simultaneous influence of capital, technology, fishing time and fishing experience on fishermen's income in the Seribu Islands. This research is quantitative research with multiple linear regression quantitative descriptive data analysis methods. The analysis results show that the variables capital and time at sea have a significant effect on fishermen's income in the Seribu Islands, while the fishing experience variable does not have a significant effect on the income of fishermen in the Seribu Islands. Then capital, technology, time at sea and sea experience simultaneously have a significant effect on the income of fishermen in the Seribu Islands. Based on research findings it is hoped that fishermen can increase their capital by extending their fishing time and traveling further to optimize their results. It is hoped that the Seribu Islands Government can contribute to policy-making and provide more attention to fishermen by providing support, guidance, and guidance on how to increase fishing.